دراسة الطيف الغذائي عند سمكة الجيجة Trigla lastoviza ((Bonnaterre,1788 في المياه البحرية لمحافظة اللاذقية / سوريا - الحصني, زينة; المجيد, زهير; الشيخ رشيد, ريم (Latakia University Journal -Biological Sciences Series, 2019)
This study presents scientific results on the feeding habit of Trigla lastoviza, which is considered as economically important fish species in Syria, lives on rocky, sandy or muddy bottoms and can be found from time to time in waters up to 150 m. This study was conducted on 161 Trigla lastoviza caught from the marine waters of Lattakia Governorate (Borg Islam), using local gears, during the period from 16/6/2017 to 22/5/2018. The study shows that Trigla lastoviza is carnivorous and feeds on crustaceans particularly Decapoda, Penaeus was the main food, followed by the crabs(Charybdis) then by the crabs species (Lio carcinus, Carinus mediterraneus, Erphia sp. , gracilipes) and lobsters. The results show that the feeding habit of Trigla lastoviza didn't show significant qualitative differences between seasons but it shows clear quantitative differences between winter and summer seasons. تقدم هذه الدراسة نتائج علمية حول الطيف الغذائي للنوع Trigla lastoviza، حيث تعد من الأسماك الهامة اقتصادياً في سوريا, تعيش على القيعان الصخرية أو الرملية أو الموحلة، يمكن العثور عليها من وقت لآخر في المياه الضحلة حتى أعماق تصل إلى 150 م. أُجريت هذه الدراسة على (161) فرداً من أسماك الجيجة المصطادة من المياه البحرية لمحافظة اللاذقية (برج إسلام), بوسائل الصيد المحلية, خلال الفترة من16/6/2017 إلى 22/5/2018 واستخدم عدد من المعاملات المتبعة عالمياً في الدراسة . بينت الدراسة أن أسماك Trigla lastoviza لاحمة تتغذى على القشريات وبشكل خاص رتبة عشاريات الأرجل Decapoda، حيث أتت في المرتبة الأولى الجمبريات (Penaeus) تلتها السرطانات من جنس (Charybdis) وبعدها بنسب متقاربة وأقل أهمية كل من السرطانات Lio carcinus, Carsinus mediterraneus, sp. Erphia , Paguritta gracilipes و الكركند. بينت النتائج أن الطيف الغذائي لأسماك Trigla lastoviza لا تبدي فروقات نوعية كبيرة خلال فصول السنة ككل بينما تبدي فروقات كمية واضحة بين فصلي الشتاء والصيف.